2018
DOI: 10.1111/bcpt.12970
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Risperidone‐Induced Insulin Resistance in Children and Adolescents with Autism Spectrum Disorder

Abstract: The purpose of this study was to explore the association of genetic polymorphism of genes related to pharmacokinetics or pharmacodynamics with insulin resistance in children and adolescents with autism spectrum disorder (ASD) and treated with risperidone. All 89 subjects underwent measurement of fasting blood glucose and insulin levels, body-weight and height. Genotyping was performed by TaqMan real-time polymerase chain reaction (PCR) (pharmacokinetics genes: cytochrome P450 2D6 (CYP2D6) *4 (rs3892097), *5 (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
1
13
0
1
Order By: Relevance
“…However, the relation of ABCB1 1236C>T with overweight/obesity did not survive Bonferroni correction ( Table 6). The current study supports prior reports that did not find associations between ABCB1 1236C>T, 2677T>A, and 3435C>T polymorphisms with the risperidone response (Nuntamool et al, 2017), with metabolic abnormality/insulin resistance (Sukasem et al, 2018), or with steady-state plasma concentrations of risperidone or 9-hydroxyrisperidone (Yasui-Furukori et al, 2004). However, here further discrepancies are apparent in the literature, where the ABCB1 1236C>T polymorphism showed a significant association with response to risperidone (Xing et al, 2006) and an observed effect of the ABCB1 2677G>T and 3435C>T polymorphisms on risperidone-induced weight gain in patients with schizophrenia (Kuzman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, the relation of ABCB1 1236C>T with overweight/obesity did not survive Bonferroni correction ( Table 6). The current study supports prior reports that did not find associations between ABCB1 1236C>T, 2677T>A, and 3435C>T polymorphisms with the risperidone response (Nuntamool et al, 2017), with metabolic abnormality/insulin resistance (Sukasem et al, 2018), or with steady-state plasma concentrations of risperidone or 9-hydroxyrisperidone (Yasui-Furukori et al, 2004). However, here further discrepancies are apparent in the literature, where the ABCB1 1236C>T polymorphism showed a significant association with response to risperidone (Xing et al, 2006) and an observed effect of the ABCB1 2677G>T and 3435C>T polymorphisms on risperidone-induced weight gain in patients with schizophrenia (Kuzman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…After scanning the titles and abstracts, 62 articles relevant to present subject were identified for full-text scrutiny. Several studies were excluded as they did not have necessary data (11 studies) [20][21][22][23][24][25][26][27][28][29][30] ; lack of healthy controls (6 studies) [31][32][33][34][35][36] ; sample source is not peripheral blood (5 studies) 18,[37][38][39][40] ; samples derived from postmortem brain (3 studies) 10,11,41 ; participants were adults (3 study) 16,42,43 ; had patient samples that overlapped with another studies (1 study) 44 ; neurotrophic factors were studied in less than 3 articles (1 study) 19 and non-English publication (1 studies) 45 . Therefore, a total of 31 studies met the criteria were included for this meta-analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin acts by directly regulating pancreatic β cells and insulin-sensitive tissues, independent of its effects on adiposity 39. In our previous study on children and adolescents with autistic spectrum disorders, we demonstrated that risperidone therapy directly and adversely affects glucose homeostasis by inhibiting the actions of leptin and insulin 40,41. Studies on mice conducted by Cheng et al revealed that palmitic acid and arachidonic acid can inhibit leptin signaling in the paraventricular nucleus of the hypothalamus, attenuating the central leptin regulation of glucose homeostasis 42,43.…”
Section: Discussionmentioning
confidence: 95%